Single Fiber Reflectance Spectroscopy for the Monitoring of Cement Paste - Pedro M. da Silva; Luís C. C. Coelho; José M. M. M. de Almeida (Chemosensors, 2021)
Reinforced concrete structures are an essential part of our modern society, and monitoring their structural health is of paramount importance. Early detection of decay allows for the reduction of repair costs and, more importantly, the prevention of catastrophic failure. For this purpose, a single fiber reflectance spectrometer was embedded in cement paste samples for the monitoring of water at the fiber tip through its sensitivity to changes in the refractive index. It monitored the curing of samples with different water-to-cement ratios (w/c), between 0.45 and 0.60, measuring the water exhaust during the hardening of the cement paste. It also measured the capillary coefficient from cement paste samples of 0.50, 0.55 and 0.60 w/c: 0.668 ± 0.002 mm/√h, 1.771 ± 0.052 mm/√h and 6.360 ± 0.269 mm/√h, respectively. The capillary coefficient values agree with gravimetric measurements of sorptivity and are further confirmed through porosity measurements made with a scanning electron microscope. Thus, single fiber reflectance spectroscopy can be a gateway to inexpensively measure the entire life cycle of cement, from its curing until its eventual decay, assessing, in situ, its durability through the capillary coefficient.